Role of hydrometallurgy and nanotechnology in environmental protection - Srećko Stopić; Bernd Friedrich (Zaštita Materijala, 2016)
Hydrometallurgy, sometimes called leaching, includes the selective dissolution of metals from their ores, concentrates and waste materials. Metal winning requires an individually optimized process based on acceptable productivity as well as on high selectivity processing steps. The decision whether to use hydrometallurgy and pyrometallurgy depends on various concerns including an environmental impact and project costs. Hydrometallurgy offers a wide range of leaching alternatives allowing high, cleaner environment with highly effective and pollution control methodology. Compared to pyrometallurgical off gas volumes are significantly reduced, but waste water treatment becomes critical point. In this work some hydrometallurgical processes shall be described such as high pressure dissolution in an autoclave and an agitation leaching. Nanotechnology belongs to the key innovative technology for powder production and mostly used in modern life. According to Environmental Protection Agency 'Nanotechnology offers the possibility of changing the manufacturing process in two ways: 1) drastical reduction of waste products via controlled manufacturing process and 2) the use of nanomaterials as catalysts for greater efficiency in current manufacturing process by minimizing the use of toxic materials and the generation of undesirable by-products and effluents. Ultrasonic spray pyrolysis is a versatile method for the formation of nanosized particles of metals, oxides and composites. This work deals with nanoparticles of Ag, Cu and Cu and core-shell particles of RuO2/TiO2 formed by ultrasonic spray pyrolysis. Metallic nanoparticles have important role in modern life. Nanosilver is used as an antibacterial material in filters for air and water purification, also in t-shirts, as well as conductive nanoinks for printed circuits, sensors and catalysts.